Jinn Possession; a Case Report Exploring Symptom Formation in Trans-Cultural Psychiatry - Georgina Edgerley-Harris; Mohammad Arbabi; Nilesh Tirbhowan (BJPsych Open, 2025)
Aims: We report on an Afghan refugee is in his 30s who presented to a Community Mental Health Recovery Service (CMHRS) with a two year history of visual and auditory disturbances and distressing persecutory beliefs revolving around 'Jinn'. This led to significant distress, a decline in functioning and shared experience with his wife also complaining of similar events.